STUDY OF SINGLE- AND DOUBLE-MOMENT MICROPHYSICS SCHEME IMPACT ON LILI AND MANGGA TROPICAL CYCLONE - Fazrul Rafsanjani Sadarang; Destry Intan Syafitri J. (Pusat Penelitian dan Pengembangan BMKG, 2022)
In this study, prediction of tropical cyclones using the Weather Research and Forecasting (WRF) model was used to test the double-moment (DM) and single-moment (SM) microphysical parameterization schemes in event of Lili and Mangga Tropical Cyclones. Models with microphysical parameterization schemes WDM5, WDM6, WSM5, WSM6, and without microphysical parameterization schemes (CTL) were each tested against track predictions, the pressure value, and maximum wind speed. The results of track prediction show that the best schemes in the tropical cyclone case of Lili and Mangga is WSM6 and WDM6, respectively, with an average error value of 78.1 and 80.1 km. Based on the Taylor diagram, the prediction results of the pressure value and the maximum wind speed in case of Lili Tropical Cyclones get the WDM6 scheme as the best scheme. Meanwhile, the results of the pressure prediction at the cyclone center in the case of Mangga Tropical Cyclones show that the WDM6 scheme is the best. However, the prediction of maximum wind speed in Mangga tropical cyclones produces the CTL scheme as the best scheme. This study shows that DM dan SM microphysical parameterization schemes have a big impact on track prediction compare to pressure value and maximum wind speed variable.